Innovative approaches of the environmental education with the use of urban organic residues - Yépez Chávez, Alisson (2020)
This document arises from the need to strengthen environmental education in the educational field through the use of organic waste, which are seen as waste and generators of environmental, economic and social problems. The importance of environmental education as an essential tool to raise awareness and sensitize, especially to achieve the empowerment of students and promote an ecological culture. The purpose of this article is to analyze the opportunities for environmental education focused on the use of organic waste generated at the urban level. Evaluate formal environmental education in different target groups and the relationship of their learning with ICT (Information and Communication Technologies) and social networks. Its main contribution is a presentation of the reality of environmental education in the country and in different cultural contexts. The methodology used in the study is based on bibliographical research, of an expository nature; In addition, information is collected on the shortcomings and educational projects in Ecuador on environmental issues.